2020
DOI: 10.1177/1744806920927284
|View full text |Cite
|
Sign up to set email alerts
|

Persistent proliferation of keratinocytes and prolonged expression of pronociceptive inflammatory mediators might be associated with the postoperative pain in KK mice

Abstract: Epidermal keratinocytes play a vital role in restoration of the intact skin barrier during wound healing. The negative effect of hyperglycemia may prolong the wound healing process. Epidermal keratinocytes have been demonstrated to modulate and directly initiate nociceptive responses in rat models of fractures and chemotherapy-induced neuropathic pain. However, it is unclear whether epidermal keratinocytes are involved in the development and maintenance of incisional pain in nondiabetic or diabetic animals. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the vehicle-treated group, plantar incision-induced pain behaviors were similar to that observed in our previous study. 13 Strikingly, 1% capsaicin pretreatment prevented the expression of postoperative pain after plantar incision, indicating that capsaicin induced a preemptive analgesic effect. These findings are in line with previous results.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the vehicle-treated group, plantar incision-induced pain behaviors were similar to that observed in our previous study. 13 Strikingly, 1% capsaicin pretreatment prevented the expression of postoperative pain after plantar incision, indicating that capsaicin induced a preemptive analgesic effect. These findings are in line with previous results.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study showed that postoperative pain was associated with a significant increase in PCNA in the epidermis around the plantar incision site. 13 Capsaicin was reported to display anti-proliferative activity, such as inhibiting the proliferation of human small-cell lung cancer and breast cancer. 22 , 23 Capsaicin was shown to reduce the activation of epidermal cell proliferation around the incision site in the hairy skin of rats, 24 but it did not impact wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to CRPS, a proliferation of KCs and an increased release of IL-1β, IL-6, and TNFα were observed in a murine incisional model for postsurgical pain (Clark et al, 2007;Guo et al, 2020). These changes were more persistent in diabetic mice, in associations with a prolonged postoperative pain hypersensitivity (Guo et al, 2020).…”
Section: Stimulation Of Keratinocytes By Neuropeptidesmentioning
confidence: 99%